2022
DOI: 10.3390/bs12060164
|View full text |Cite
|
Sign up to set email alerts
|

Is Heterogeneity Better? The Impact of Top Management Team Characteristics on Enterprise Innovation Performance

Abstract: Although the importance of the top management team’s characteristics has attracted research attention, its influence remains undetermined. This paper considers the influence of top management team characteristics’ heterogeneity on GEM-listed enterprises’ innovation performance. From the perspective of optimizing top management team human capital and improving enterprise innovation performance, this study analyzes 634 GEM-listed enterprises via regression analysis. The results show that the effect of shallow-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Upper echelons theory suggests that demographic (surface-level) characteristics can act as proxies for deep-level differences (Hambrick and Mason, 1984). Surface-level characteristics act as a stand-in for cognitive resources and personal, difficult to discern, characteristics (Jackson et al , 1995; Soleimani and Stauffer, 2022; Wang et al , 2022). For instance, research using upper echelons theory has demonstrated linkages between the demographic characteristics of a firm’s leaders and organizational decisions and outcomes (Finkelstein et al , 1996; Javed et al , 2023; Roberson and Hyeon, 2007; Schumann et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Upper echelons theory suggests that demographic (surface-level) characteristics can act as proxies for deep-level differences (Hambrick and Mason, 1984). Surface-level characteristics act as a stand-in for cognitive resources and personal, difficult to discern, characteristics (Jackson et al , 1995; Soleimani and Stauffer, 2022; Wang et al , 2022). For instance, research using upper echelons theory has demonstrated linkages between the demographic characteristics of a firm’s leaders and organizational decisions and outcomes (Finkelstein et al , 1996; Javed et al , 2023; Roberson and Hyeon, 2007; Schumann et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They were all engaged in research in the elds of public health, emergency management, and disaster relief, and held positions in management and technical posts, with in-depth understanding and unique views on rescue work. A group composed of experts from different professions and professional elds will have deeper and broader discussions than any group composed of experts from the same eld, and can produce more scienti c results [11]. Therefore, the evaluation model generated in this study can be applied to the actual evaluation of bioterrorism work management, personnel quality, and the operational ability of the rescue team.…”
Section: Selection Of Expertsmentioning
confidence: 99%
“…The environmental identity of TMT is the extent to which the TMT's self-conceptualizes toward the environment, and a TMT who has a high level of environmental identity will affect a company's strategic choice [38]. In addition, based on upper echelons theory [39], a TMT's decision-making processes are caused by supervisors' characteristics, and leadership is a key characteristic of a supervisor [40][41][42][43], supporting the mediating role of environmental identity. Indeed, as discussed above, sustainable leadership promotes the environmental identity of the TMT, and the environmental identity of the TMT will influence a company's strategic choice.…”
Section: The Mediating Role Of the Environmental Identity Of The Tmtmentioning
confidence: 99%